Change in the primary solidification phase from fcc to bcc-based B2 in high entropy or complex concentrated alloys. (15th January 2017) - Choudhuri, D.; Gwalani, B.; Gorsse, S.; Mikler, C.V.; Ramanujan, R.V.; Gibson, M.A.; Banerjee, R.
Abstract: An examination of a compositionally graded Alx CuCrFeNi2 high entropy alloy (HEA) or complex concentrated alloy (CCA), revealed that marginally increasing Al content from x = 0.8 to x = 1.0 (+ 6 at.%) changes the primary solidification phase from a simple disordered- fcc to a bcc -based ordered-B2 phase. Subsequently, a second solidification product forms, a disordered- bcc in case of x = 0.8 and a disordered- fcc in case of x = 1.0. Solid-state decomposition within these phases results in fcc + L12 and bcc + B2 products, accompanied by compositional partitioning. These results provide new insights into the influence of Al on the primary solidification product, and have been rationalized using a computational thermodynamic approach. Graphical abstract: